2022
DOI: 10.1109/tits.2022.3155175
|View full text |Cite
|
Sign up to set email alerts
|

AICP: Augmented Informative Cooperative Perception

Abstract: Connected vehicles, whether equipped with advanced driver-assistance systems or fully autonomous, are currently constrained to visual information in their lines-of-sight. A cooperative perception system among vehicles increases their situational awareness by extending their perception ranges. Existing solutions imply significant network and computation load, as well as high flow of not-always-relevant data received by vehicles. To address such issues, and thus account for the inherently diverse informativeness… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 61 publications
(53 reference statements)
0
7
0
Order By: Relevance
“…Such information could be distributed in a similar way to the cooperative perception mechanism, where each platoon member would also include in its message the information on the known other members’ parameters. Additionally, messages could be filtered before being relayed, e.g., based on their age or their relevance in the adaptation process, similarly to the approach proposed in [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Such information could be distributed in a similar way to the cooperative perception mechanism, where each platoon member would also include in its message the information on the known other members’ parameters. Additionally, messages could be filtered before being relayed, e.g., based on their age or their relevance in the adaptation process, similarly to the approach proposed in [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, Zhou et al suggested an enhanced cooperative information perception, in which an ultra-fast fltering system is proposed to optimize the received data. Tis means that, after fltering, only the information important for vehicle navigation is displayed, thereby eliminating visual noise and facilitating the understanding of the environment [48]. Additionally, an interesting approach was proposed by Cui et al where a tilt model is obtained based on intervehicle perception; in other words, frst, the information is encoded in a point-based representation to transmit compact messages between vehicles; secondly, the 3D LiDAR data from the diferent vehicles are aggregated and fnally analyzed [49].…”
Section: Cooperative Perceptionmentioning
confidence: 99%
“…Specifically, ETSIs defines the message format and rules for CPMs generation [32,33]. In this way, CPMs allows CAVss to share surrounding information (e.g., objects detected) detected by sensors, such as, cameras, RADAR, LIDAR, and others [34,35]. A CPM contains data about the vehicle that generated the CPM, its onboard sensors (e.g., range and FoV), as well as data about the detected object (e.g., position, speed, distance, and size) [22,27].…”
Section: Cp Overviewmentioning
confidence: 99%